Synthesis, structural analysis, chemical stability, magnetic study and electric percolative effect on composite GdBa2Cu3O7−δ /Sr2GdSbO6 - Montana Quintero, Nilzon (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This document reports the synthesis of the materials Sr2GdSbO6(SGSO) and GdBa2Cu3O7 −δ (GBCO), by the reaction method in solid state and GdBa2Cu3O7−δ/Sr2GdSbO6 (GBCO/SGSO) composites in different volumetric proportions. The structural characterization of the synthesized compounds was carried out by means of X-ray diffraction, using the Rietveld refinement method, performing a quantitative analysis of phases in volume. The results obtained confirm that the two materials (GBCO / SGSO) are chemically stable, coexisting in the same volume at 900C. It was also found, by means of magnetization measures, that the GBCO contained in each one of the different composites, It keeps superconducting properties, as the transition to the superconducting state was obtained below a temperature of 90K. The morphological characterization was performed by scanning electron microscopy (SEM) and elemental analysis by means of dispersive energy spectroscopy (EDX) measurements. The electrical study was performed by means of voltage measurements as a function of the current at room temperature and subsequent calculation of the volumetric resistivity. The study of the percolative effect was carried out by calculating the critical volume and the critical exponents in each one of the insulating and conductive phases, using the Kussy model [1] and the semi-classical non-linear response model Random Resistor cum Tuning Bond Network (RRTN)[2], by contrasting critical exponents with those found in the literature